Drunken moon. - Teo, Raymond Say Kiam. (2009)
The art of crafting stories for Animation production are extremely crucial. It consists of key elements in creating dynamic characters, stories, and environments. Technically, it also reviews different mediums, methods, structures and styles of create creation.